2021
DOI: 10.1371/journal.pone.0234587
|View full text |Cite
|
Sign up to set email alerts
|

Trends and gaps in the use of citizen science derived data as input for species distribution models: A quantitative review

Abstract: Citizen science (CS) currently refers to the participation of non-scientist volunteers in any discipline of conventional scientific research. Over the last two decades, nature-based CS has flourished due to innovative technology, novel devices, and widespread digital platforms used to collect and classify species occurrence data. For scientists, CS offers a low-cost approach of collecting species occurrence information at large spatial scales that otherwise would be prohibitively expensive. We examined the tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 108 publications
1
45
0
1
Order By: Relevance
“…Sesleria albicans-Galium sterneri calcarious grassland (Figure S1), U17 Luzula sylvatica-Geum rivale tall-herb community (Figure 4) and M17 Scirpus cespitosus-Eriophorum vaginatum blanket mire (Figure S11) were all predicted with relatively high accuracy (TSS 0.820 or above). All three contain plant species included in the national Red Data List for vascular plants (Stroh et al, 2014) (Feldman et al, 2021) and while biases may arise due to spatial variation in collection efforts or taxonomic skill (Robinson et al, 2018) there is evidence that they can provide an invaluable resource for applied ecologists with both pre-processing to ensure data quality (Isaac et al, 2014) Of key importance is that the plant species that volunteers are asked to focus on were derived from the weighted occurrence of species within the NVC system, so as to be representative of each community, while at the same time avoiding species that would be taxonomically challenging for amateur botanists. This is termed the 'wildflower level' of participation to minimise identification errors (Pescott et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sesleria albicans-Galium sterneri calcarious grassland (Figure S1), U17 Luzula sylvatica-Geum rivale tall-herb community (Figure 4) and M17 Scirpus cespitosus-Eriophorum vaginatum blanket mire (Figure S11) were all predicted with relatively high accuracy (TSS 0.820 or above). All three contain plant species included in the national Red Data List for vascular plants (Stroh et al, 2014) (Feldman et al, 2021) and while biases may arise due to spatial variation in collection efforts or taxonomic skill (Robinson et al, 2018) there is evidence that they can provide an invaluable resource for applied ecologists with both pre-processing to ensure data quality (Isaac et al, 2014) Of key importance is that the plant species that volunteers are asked to focus on were derived from the weighted occurrence of species within the NVC system, so as to be representative of each community, while at the same time avoiding species that would be taxonomically challenging for amateur botanists. This is termed the 'wildflower level' of participation to minimise identification errors (Pescott et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our data set for studying biodiversity science production in the region was based on the use of Bio-Dem as a platform that is fed solely by the data presented in the GBIF, and the V-Dem research project. There are other initiatives of citizen science platforms that could be taken into consideration, especially in regards to species records (Feldman et al, 2021 ). Our bibliometric analysis had some limitations that are worth pointing out.…”
Section: Discussionmentioning
confidence: 99%
“…This tool allowed us to explore the relationship between Central American species occurrence records from the Global Biodiversity Information Facility (GBIF) ( www.gbif.org ) and the region's political framework from the Varieties of Democracy (V-Dem) database ( www.v-dem.net ) from 1960 to 2020 (Coppedge, 2020 ; Zizka et al, 2021 ). Geo-referenced species occurrence records deposited in GBIF have become crucial for biodiversity research and data modeling (Feldman et al, 2021 ), while V-Dem is the world's largest database dedicated to the collection and conceptualization of democracy data (Coppedge, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Focusing on little more than 100 species of Basidiomycota (no milkcaps, though), Ascomycota, rusts and lichens, LAFF resulted in a dataset of over 1500 records of 77 species, some of which (e.g., Godronia fuliginosa and Sporomega degenerans) have been rediscovered after a recording gap of over 50 years. Notwithstanding these virtuous examples, a recent analysis of the use of citizen science as a source of data for species distribution models has revealed "a notable under-use of plant, fungi, lichen and bryophyte public databases in the last decade in papers that model the distribution of species, as compared to the interest that they generate in CS [citizen science] programs", a fact attributed by authors to the difficulty of identifying species of these taxonomic groups in the field [90]. For what concerns macrofungi, the best success stories mentioned above have clearly indicated that a strict collaboration between professional and amateur mycologists is paramount in order to build reliable datasets, to be used as a robust basis for conservation mycology initiatives (even iNaturalist has 'identifiers').…”
Section: Milkcaps Distribution Datamentioning
confidence: 99%